Stratigraphical and paleoenvironmental features of the Pleistocene sediments of M. Mario (Rome) - L. Bergamin; F. Marra; I. Palagi; CARBONI, Maria Gabriella; DI BELLA, Letizia (BIRKHAUSER VERLAG AG, 2000)
The marine succession of Monte Mario (Rome) has been considered a classical section of the Plio-Pleistocene boundary and the related transgressive phase in Italy. A detailed micropaleontological study on the Monte Mario marine subsurface succession permitted to re-interpret the stratigraphy and the evolution of the basin. Here, we present the results achieved by means of data supplied by three boreholes. The composite section, 90 m thick, includes clay and sand deposits previously attributed to the Pliocene and early Pleistocene. The Pliocene age assignment, previously attributed to the lower richly fossiliferous marine clayey unit, located under the Arctica islandica level, is refuted. New data from foraminifers and ostracods allow us to refer the entire succession to the Pleistocene, for the presence of Globigerina calabra, G. ca, ia coensis and Loxoconcha turbida. Consequently, the well-known Arctica islandica level, a local marker bed, may no longer be considered the transgressive unit marking the beginning of the Pleistocene cycle. The paleoecological study evidenced a gradual shallowing from upper circalittoral, with low dissolved oxygen values (VTC), to sandy oxygenated infralittoral environment, sometimes characterised by vegetate bottoms. The evolution of the basin seems controlled by tectonics more than by glacioeustatism. In fact, palinspastic restoration of the investigated sequence and the presence of reworked Pliocene foraminifers allowed us to relate the observed sea level changes to regional tectonic phases and to infer no direct influence of climate on the transgression.